THE GUIDELINES FOR RESULT - BASED MANAGEMENT OF SCHOOL ADMINISTRATORS OF UDON THANI EDUCATIONAL OPPORTUNITY EXPANSION SCHOOLS - Laolapa, Saifon; Wongaree, Sunisa; Homsin, Nawattakorn (Journal of MCU Nakhondhat, 2023)
The purposes of this research was: 1) to study the guidelines for Result-Based Management of the school administrators of Udon Thani Educational Opportunity Expansion Schools, and 2) to evaluate the guidelines for Result-Based Management of school administrators of Udon Thani Educational Opportunity Expansion Schools. The research method was divided into 2 phases by using mixed method research. Phase 1 was qualitative research, to study the guidelines for Result-Based Management of school administrators of Udon Thani Educational Opportunity Expansion Schools by using the semi-structured interview. The experts were five people by purposive sampling such as the experts related to educational administrations, school administrators, and teacher about the guidelines for Result-Based Management of school administrators of Udon Thani Educational Opportunity Expansion Schools Phase 2 was quantitative research, to evaluate the guidelines for Result-Based Management of school administrators of Udon Thani Educational Opportunity Expansion Schools. The experts were five people by purposive sampling. For example the doctoral graduates or other related fields, knowledgeable person/ experience in educational administration at least 5 years or 10 years, and knowledgeable person/ experience with school operations at least 10 years. The data were analyzed of the utility, suitability, possibility side and conformity and to study the guidelines for Result-Based Management of the school administrators of Udon Thani Educational Opportunity Expansion Schools. Research instruments were the semi-structured interview, and statistics used for research were mean and standard deviation. The results were as follows: 1) The guidelines for Result-Based Management of school administrators of Udon Thani Educational Opportunity Expansion School were 4 aspects as follows: reward, strategic planning of the organization, determining the details of performance indicators and performance measurement & verification respectively. 2) to evaluate the guidelines for Result-Based Management of school administrators of Udon Thani Educational Opportunity Expansion Schools found that every aspect in terms of the utility, suitability, possibility side and conformity were at the highest level.